SIKAP INDIA TERHADAP KERJA SAMA NUKLIR PAKISTAN – TIONGKOK TAHUN 2010 - 2015 - Erdaini Harfitri; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research explaining about the attitude as its reaction of India to nuclear cooperation Pakistan and Tiongkok in development of nuclear reactor Pakistan. Tiongkok as its also partner in developing the military force Pakistan. Pakistan is one of yhe large state in South Asia region which is side by side with India. India and Pakistan has involved in continuing conflict. Their conflict is so complicated begin from the conflict over Kashmir, commuunal conflict and arm race. For Pakistan , India is the biggest threat for its survival. Because of that Pakistan need to counterweight India power by improving its weapon and nuclear capabilities. In order to achieve that purpose Pakistan built good relationship with Tiongkok. Tiongkok has the besome the resources for raw material, technology and axpert for Pakistan military weapon and nuclear.The research use realism perspective of International Relations. Pluralism believe that state is the only actor in international world. India as one state in South Asia region important to build its weapon to deterence from Pakistan. The United State has the become the resources for raw funding to make the progress in India defence.This research is also guide by security regional and balancing power. The techniques used to collects data to study the case to library research in the form of journals, books, official document, article, and website. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods.Keyword: nuclear, military weapon cooperation and conflict.